Lo sguardo sul paesaggio. Una lettura di Nenhum olhar di José Luís Peixoto (Altre Modernità, 2015)
The present article analyses the novel Nenhum olhar by José Luís Peixoto (2000) from the perspective of “spatial turn” theories and “landscape studies”, taking into consideration the importance given to the gaze as a way of representing reality.